The theoretical and methodological formants of modern ecocriticism - Статкевич, Лариса Павлівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article devotes to the definition of ecocriticism formants – new methodological direction in contemporary literary studies, traces its genesis and functioning, defines the horizons in the scientific context. The author provides answers to such important in contemporary discourse of literary criticism questions such as: 1) what does ecocriticism do? 2) what is the scientific potential of ecocriticism research.